Health Risk Analysis of Mercury, Lead and Cadmium in Some Commercial Fish Species Collected from Markets in Monrovia, Liberia - Ngumbu, R.S; Voegborlo, R.B; Kwaansa-Ansah, E.E (International Journal of Advances in Life Science and Technology, 2016)
The levels and health risks of mercury (Hg), lead (Pb) and cadmium (Cd) were evaluated in twenty-nine commercial fish species collected from markets in Monrovia, Liberia. A mixture of HNO3, HClO4 and H2SO4 was used for complete oxidation of organic tissue. Total mercury was determined by cold vapor atomic absorption technique using an automatic Mercury Analyzer; while the concentrations of lead and cadmium were determined by flame atomic absorption spectrometry. Estimation of the dietary exposure of the consumers to these metals were determined based on data from the American Food Consumption Index and the associated health risks were evaluated by comparing intakes with the Provisional Tolerable Weekly Intakes (PTWIs). The hazard quotient and total hazard index for the tested metals in all the species were less than the USEPA guideline value of 1, suggesting that the consumption of the tested fish species has no adverse health effects considering exposure to the tested metals.